Covalently layer-by-layer assembled homogeneous nanolayers with switchable wettability1. Issue 25 (7th July 2015) - Topuz, Fuat; Möller, Martin; Groll, Jürgen
<x xml:space="preserve">Abstract</x> A layer-by-layer growth through alternating chemisorption of isocyanate functional star-shaped polyethers (NCO-sP(EO-stat-PO)) and a linear polymer ((PVFA-co-PVAm)) is described.